Decline of Jackdaws Corvus monedula in the city of Zielona Góra - Czechowski, Paweł; Bocheński, Marcin; Ciebiera, Olaf (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The aim of the study was to determine the number and distribution of breeding Jackdaws Corvus monedula in different urban habitat types in Zielona Góra in 2012 and to compare the results with those from a 2004 survey. On the seven study areas, the highest density was recorded in Park Tysiąclecia with 6.0 pairs per 10 ha, followed by the plot Słoneczne with 3.5, the Old Town with 1.0 and the plot Winnica with 0.4. On the plots Zacisze, Chynów and Industrial Zone, foraging Jackdaws were noted but we did not find any indication for breeding.
Keywords: wróblowe; ornitologia